Repatriation to Turkey's "safe zone" in Northeast Syria: Ankara's goals and European concerns - Sinem Adar (Stiftung Wissenschaft und Politik (SWP), 2020)
Following the US decision to withdraw troops from Northeast Syria and upon separate agreements with the US and Russia, Ankara established what it calls a safe zone in the area between Tal Abyad and Ras al-Ayn. Even if spanning a smaller territory than envisaged, Turkey aims with its safe zone to impede Kurdish autonomy in Northern Syria, on the one hand, and to return refugees who have increasingly become a domestic policy challenge for the ruling Justice and Development Party (AKP thereafter), on the other hand. Turkey's plan for repatriation signals that its interests align with European interests in refugee return. Given concerns about the safety of refugees, voluntary nature of return, and Ankara's attempts at demographic engineering, Europeans should not support a Turkey-led repatriation to Syria without conditions.
Keywords: 320